PENDIDIKAN MODERASI BERAGAMA DALAM AL-QUR'AN DAN HADITS - Fathoni (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2021)
Islam as a divine religion in addition to teaching its followers to be obedient and obedient to its teachings but also teaches moderation towards other religions. In addition to moderation in matters of worship, it is also moderate in social life. Religious moderation is an interesting study because it is an integral core of Islamic teachings, Islam does not allow its people to carry out religious coercion. In a verse it is stated